Study of the Metabolic Profile in Buffaloes with Prolonged Anestrus - Adrian Bota; Horatiu Bujdei; Remus Chiorean (Scientific Papers Animal Science and Biotechnologies, 2023)
The metabolic profile test in animals is used to assess their nutritional status, to diagnose disease and assess fertility. The aim of this paper was to investigate the metabolic profile in buffalo cows. Forty buffaloes from the Research and Development Station for Buffaloes Secaia - Romania, were divided into two groups (20 heads/group). Estrus induction protocols were applied to the first group (G1), while the second group consisted of buffalo cows that express natural oestrus (G2). When the artificial insemination was performed, blood samples were taken and the following parameters were determined: hemoglobin, total serum protein, phosphorus, calcium, magnesium, alkaline phosphatase, cholesterol, glucose, lipase, urea. G2 buffalo cows had significantly higher concentrations of hemoglobin, serum protein, glucose and inorganic phosphorus, while the serum calcium levels were lower in the group. The concentration of magnesium, alkaline phosphatase, cholesterol, lipase and urea did not differ significantly between the buffalo groups (p>0.05). The Ca:P ratio for G2 buffaloes was lower (1.94:1) compared to G1 buffaloes (2.89:1). It can be concluded that the level of hemoglobin, serum protein, glucose, calcium and inorganic phosphorus plays a major role in the reproduction of buffaloes.